Formulation and evaluation of prazosin hydrochloride loaded solid lipid nanoparticles: PRAZOSIN HYDROCHLORIDE LOADED SOLID LIPID NANOPARTICLES - Bandgar, Sandip Akaram; Dhavale, Pranali; Patil, Pravin; Shelake, Sardar; Patil, Shitalkumar (Journal of Drug Delivery and Therapeutics, 2018)
Solid Lipid Nanoparticles (SLN) are rapidly developing field of nanotechnology with several potential application in drug delivery and research. Drugs having low aqueous solubility not only give low oral bioavailability but provide high inter-and intra subject variability. The purpose of the present study was to investigate the bioavailability enhancement of Prazosin Hydrochloride drug by formulating solid lipid nanoparticle. Prazosin Hydrochloride Drug is an antihypertensive drug with limited bioavailability so that solid lipid nanoparticle (SLN) is one of the approaches to improve bioavailability. SLN were prepared using glyceryl monostearate by hot homogenization followed by Solvent emulsification-ultrasonication. Prazosin Hydrochloride loaded SLN were characterized and optimized by parameters like particle size, zeta potential, XRD, DSC. Proposing Hydrochloride loaded SLN having the particle size 263.8±1.88 and entrapment efficiency 89.29±0.65% shows better bioavailability and optimum stability in studies. The SLN studies prepared using glyceryl mono stearate   as a lipid and Polaxamer 407 as a polymer leads to improve bioavailability of the drug.Keywords: Prazosin Hydrochloride, Solid Lipid Nanoparticles, Entrapment efficiency, DSC